The Role of Coach's Gender on Coaching Self-Efficacy for Division III Female Student-Athletes - Swim, Nicholas; Walker, Khirey; Turick, Robert; Judge, Lawrence (Bowling Green State University, 2021)
The landscape of women in college sports has improved dramatically since the enactment of Title IX in 1972. Participation rates and funding have increased, providing a more inclusive environment for female student-athletes to compete. However, females ascending to leadership positions within the NCAA has experienced a downward trend. Currently, males hold the majority of athletic director positions and serve as head coaches on over half of female varsity sport teams. This may be detrimental to female student-athletes as women in leadership positions provide same-gender role models and mentors relationships for female student-athletes. The purpose of this study is to examine the relationship between coaching gender and perceived self-efficacy of female student-athletes to pursue coaching as a profession, while also investigating the impact of perceived barriers (discrimination and working hours) to entering the field. The sample population, Division III female student-athletes (n=192), regardless of their coach's gender, indicated having high coaching self-efficacy. Additional findings found that coaching self-efficacy had a statically significant relationship with gender (p=.48), desire to coach (p